2017
DOI: 10.1080/15459624.2017.1422870
|View full text |Cite
|
Sign up to set email alerts
|

A task-based analysis of black carbon exposure in Iowa farmers during harvest

Abstract: Diesel exhaust has been associated with adverse human health effects. Farmers are often exposed to diesel exhaust; however, their diesel exposure has not been well characterized. In this descriptive study, we measured black carbon concentrations as a proxy for diesel exhaust exposure in 16 farmers over 20 sampling days during harvest in southeast Iowa. Farmers wore a personal aethalometer which measured real-time black carbon levels throughout the working day, and their activities were recorded by a field rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Our results show that increased proximity to diesel engine exhaust sources and indoor work are the main determinants of BC exposure levels. This finding is supported by Stapleton et al (2018) and Sauvé et al (2020). They analyzed farming activity and reported that BC exposure levels increased when close to diesel-powered equipment indoors.…”
Section: Accepted Manuscriptmentioning
confidence: 66%
See 2 more Smart Citations
“…Our results show that increased proximity to diesel engine exhaust sources and indoor work are the main determinants of BC exposure levels. This finding is supported by Stapleton et al (2018) and Sauvé et al (2020). They analyzed farming activity and reported that BC exposure levels increased when close to diesel-powered equipment indoors.…”
Section: Accepted Manuscriptmentioning
confidence: 66%
“…Farmers who used or worked near diesel vehicles were reported to be exposed to GMs of BC exposure ranging from 0.5 µg m -3 while harvesting to 4.9 µg m -3 during animal work. Higher GMs were found for increased proximity to diesel-fueled vehicles and equipment (2.9 vs. 0.3 µg m -3 ) (Stapleton et al, 2018). A 68% increase in BC concentration was predicted when working near diesel-powered vehicles compared to far proximity (Sauvé et al, 2020).…”
Section: Accepted Manuscriptmentioning
confidence: 89%
See 1 more Smart Citation
“…Farmworkers are exposed to numerous air pollutants, including black carbon, particulate matter, carbon monoxide, nitrogen dioxide, sulfur dioxide, and diesel-related emissions from farm activities, such as tractor driving, maintenance and repair of machinery and equipment, and agricultural crop residue burning (122,134). These exposures increase the risk of adverse respiratory and cardiopulmonary outcomes among farmworkers, including lung cancer, wheeze, asthma, and chronic obstructive pulmonary disease (COPD) (63,122,134).…”
Section: Air Pollutionmentioning
confidence: 99%
“…Absorbance-based optical monitors, such as an Aethalometer, have been used for near-real time monitoring of black carbon (BC). , Correlation was found between the BC concentration obtained from the Aethalometer and EC concentration determined by NIOSH Method 5040. However, a workplace-specific conversion factor is required for more accurate EC estimates as light attenuation in this optical technique is influenced by the particle morphology, filter loading, varying refractive indices, and scattering by other sample components, and possible absorption of non-EC materials.…”
mentioning
confidence: 99%